Research on IQ Imbalance Error of Orthogonal Alternating Sampling. (4th March 2022) - Luo, Junyi; Liu, Tao
Abstract : In the signal acquisition of complete orthogonal frequency alternating acquisition system, we need to transform the broadband input signal to baseband through analogue orthogonal demodulation. Thus, the IQ imbalance errors will inevitably exist, including amplitude imbalance error and phase imbalance error, resulting in distortion deterioration of reconstruction signals. This paper makes an in-depth study on such IQ imbalance errors and mathematically deduces the mathematical expressions of imbalance errors and the spurious frequency distribution caused by them, which shows that the positions where the spurious signals appear are closely related to the frequency of input signal and the tuning frequency of analogue quadrature demodulation. Meanwhile, the amplitude and phase imbalance parameters of the channels I and Q are also calculated. Finally, the spurious effects caused by imbalance errors are verified by simulation experiment, and the verification results are consistent with the theoretical derivation results.